Skin Sensitivity Assessment Using Smartphone Haptic Feedback - Wilson O. Torres; Michael E. Abbott; Yuqing Wang; Hannah S. Stuart (IEEE Open Journal of Engineering in Medicine and Biology)
Goal: This work presents a smartphone application to assess cutaneous sensory perception by establishing Vibrational Perception Thresholds (VPTs). Cutaneous sensory perception diagnostics allow for the early detection and symptom tracking of tactile dysfunction. However, lack of access to healthcare and the limited frequency of current screening tools can leave skin sensation impairments undiscovered or unmonitored. Methods: A 23-participant cross-sectional study in subjects with a range of finger sensation tests Smartphone Established VPTs (SE-VPTs) by varying device vibrational intensity. These are compared against monofilament test scores, a clinical measure of skin sensitivity. Results: We find a strong positive correlation between SE-VPTs and monofilament scores ( $r_{s}$ = 0.86, p = 1.65e-07). Conclusions: These results demonstrate the feasibility of using a smartphone as a skin sensation screening tool.